1999
DOI: 10.1055/s-2007-1013171
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Aspergilloma - Clinical Findings and Surgical Treatment

Abstract: The management of pulmonary aspergilloma is still a topic of discussion. Demonstrating several cases of pulmonary aspergilloma, their clinical course and their follow-up, we try to contribute some arguments for the preference of an early operation. Between 1992 and 1998, 18 patients underwent thoracotomy for treatment of pulmonary aspergilloma. The most common indication for operation were hemoptysis [6] and indeterminate mass [6]. Lobectomy was the most frequent operation [11]. Underlying diseases were bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
9
0
4
Order By: Relevance
“…13,15 Recent investigators reported a morbidity rate of 25% and a mortality rate of 5% after surgery, although the classification of postoperative complications varied (Table 4). 12,13,[16][17][18][19][20][21] The complications were massive pleural bleeding, bronchopleural fistula, empyema, and prolonged air leakage. Hypervascularization of the bronchial or intercostal arteries caused by chronic infection and dead space problems from the underlying lung disease may be related to these complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 Recent investigators reported a morbidity rate of 25% and a mortality rate of 5% after surgery, although the classification of postoperative complications varied (Table 4). 12,13,[16][17][18][19][20][21] The complications were massive pleural bleeding, bronchopleural fistula, empyema, and prolonged air leakage. Hypervascularization of the bronchial or intercostal arteries caused by chronic infection and dead space problems from the underlying lung disease may be related to these complications.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, although the surgical treatment of asymptomatic aspergilloma is still controversial, 23 pulmonary aspergillosis should be resected before the symptoms become severe if the patient is a surgical candidate. 18 18 28% 18% Babatasi 13 84 27% 4% Park 19 110 24% 1% Al-Kattan 20 20 25% 5% Kurul 21 59 32% 3% Kim 12 88 27% 1%…”
Section: Discussionmentioning
confidence: 99%
“…Нередко после эмбо лизации наблюдается повторное легочное кровотече ние, что требует консультации торакального хирурга. Оптимальным лечением в такой ситуации является хирургическая резекция, но это связано с высокой летальностью (класс рекомендаций ВII) [238][239][240][241]. Хирургические вмешательства не всегда возможны из за сопутствующей патологии и низкой легочной функции.…”
Section: аспергилломыunclassified
“…It may occur in 11% of patients with a chronic tuberculous cavity, and approximately 25%-55% of patients with aspergilloma have a history of the disease (Kim et al 2001). Patients with aspergilloma are often asymptomatic but may present with hemoptysis (Kaestel et al 1999). Plain radiography of the chest may depict a mobile, rounded mass with air-crescent ring (Fig.23.26b and 23.37a,b).…”
Section: Aspergilloma (Mycetoma)mentioning
confidence: 99%